Phytomedicine a treasure of pharmacologically active products from plants - Bhat, Rouf Ahmad 1981-; Hakeem, Khalid Rehman; Dervash, Moonisa Aslam (Academic Press, Elsevier, 2021)
Phytomedicine: A Treasure of Pharmacologically Active Products from Plants aims to present updated knowledge of plant-based medicines in terms of their research and development, production, and utilization, from the viewpoint of sustainability and by using the latest technologies. The book explores different phytometabolites on a mass scale, coupled with the efficacy, performance and applicability on target organisms to treat curable and fatal diseases.Readers will find a coherent package of phytotherapeutic information regarding inclusive assortment of research based, scientific amplitude of metabolites from the plant world encompassing various action plans. Information is presented sequentially regarding phytochemistry, biological activity and the serviceable aspects of bioactive compounds. The book also addresses various advancements and achievements of novel drugs from plants using molecular and enzymatic activities, and various technological tools in an ecofriendly fashion.- Discusses phytotherapeutic properties for a wide range of medical conditions, including anti-pyretic, anti-infective, anti-malarial, Anti-AIDS, anti-diabetic, anti-cancerous, immune-modulatory applications- Includes a discussion of synergistic effects of formulations and antagonistic drug interactions- Addresses advancements and achievements of novel plant-based drugs using molecular, enzymatic activities and various technological tools in an eco-friendly fashion